Uji Aktivitas Anthelmintik Batang Kayu Kuning (Arcangelisia flava (l.) Merr.) Terhadap Larva-3 Ascaridia galli - Melizsa Melizsa (STIKes Kharisma Persada, 2019)
Yellow wood stems (Arcangelisia flava (L.) Merr.) Are traditionally used to treat worms. Research has been carried out on the anthelmintic activity of 70% ethanol extract of yellow wood stems (Arcangelisia flava (L.) Merr) against Ascaridia galli larvae in broiler breeds of 2 weeks of age with a weight of 800-960 grams. The study used 6 groups of test animals and each group consisted of 5 chickens. Group 1 as a normal control (without infection), groups 2 - 6 were infected with 1000 infective eggs of Acaridia galli, on the 10th day after infection, continued with different treatments in each group. Group 2 as a negative control, group 3 as a positive control, group 4, 5, 6 as a group of extract solutions, with a dose of 26 mg / 400 gBB, 52 mg / 400 gBB, 104 mg / 400 gBB. Three days later all test animals were surgically removed from the intestinal mucosa to determine the number of Ascaridia galli larvae that were alive. The average number of Ascaridia galli larvae-3 that live, namely group 1; does not contain larva-3, group 2; 733 tails, group 3; 52 tails, group 4; 170 tails, group 5; 91 tails, group 6; 38 tails. The data were analyzed using one-way ANOVA, obtained F value = 103,774 greater than F table = 2,87 (α = 0,05) then followed by the Tukey test. Based on the statistical analysis data, it can be concluded that the solution of 70% ethanol extract of yellow wood stems at doses of 26 mg / 400 gBB, 52 mg / 400 gBB and 104 mg / 400 gBB has anthelmintic activity. The higher the dose given, the stronger the anthelmintic power.